Peer Support and Confidence in English Speaking Proficiency among EFL Students - Hijrinia Kusumaning Ayu; Nur Sehang Thamrin; Anjar Kusuma Dewi; Abdul Kamaruddin (MASI Mandiri Edukasi, 2026)
This study investigates the influence of peer support systems on students’ self-confidence and English as a Foreign Language (EFL) speaking proficiency. Using a quantitative survey design, data were collected from 150 English Education students from three universities in Palu, Indonesia. The questionnaire measured emotional support, feedback and correction, academic support, self-confidence, and self-perceived English-speaking skill. Data were analyzed using descriptive statistics, Confirmatory Factor Analysis (CFA), and simple linear regression in Jamovi. The findings indicate that peer support has a significant positive effect on students’ self-confidence (R² = 0.217, p < .001) and self-perceived English-speaking ability (R² = 0.283, p < .001). Furthermore, mediation analysis reveals that self-confidence partially mediates the relationship between peer support and speaking ability. Although the measurement model demonstrates marginal fit based on CFI and TLI values, the RMSEA value indicates an acceptable model fit. These results highlight the importance of supportive peer environments in fostering confidence and improving speaking proficiency in EFL contexts, particularly through informal peer interactions outside the classroom.